Economic reforms in the Bohemian era in Iraq: from the period (334-447 Ah) - Al-Maliki, Haidar Salem Mohammed (Al-Adab Journal, 2021)
The Abbasid caliphate, since its emergence on the tourism scene, which took control of the religious and political aspects of the Islamic Orient, was not subject to it continuously, as in Baghdad, among the other Hassan shows several revolutions, against it for the geographical distance from the Abbasid caliphate in Baghdad, or the emergence of princes of the caliphate, but or is it weak as a result of the takeover of weak princes, or not? The emergence of princes of strength in number and number, and at the same time the weakness of the caliphate, and this is what happened in the faith of the Bohemian Covenant, which is the subject of our discussion. When they took over the Bohemian Emirate of the Orient, and arrived in Baghdad, the economic situation deteriorated in the capital of the Abbasid caliphate, for several reasons, including that the late Abbasid era, many revolutions appeared in Baghdad, causing hunger and drought, as well as the spread of the plague, disrupting life, neglecting agriculture the basic forces of the population at that time, and causing the paralysis of the trade movement. Moreover, the Princes of The Boi's Yin did not find enough money in Baghdad, which led them to give the territories interruptions, and the emergence of revolutions rejecting them.